VD_FINDINFO Décision / 2017 / 709 vom 20. September 2017 - VD Tribunal cantonal (2017)
ORDONNANCE PÉNALE, NOTIFICATION DE LA DÉCISION, RETRAIT DU COURRIER | 354 CPP (CH), 355 al. 2 CPP (CH), 87 al. 3 CPP (CH), 87 al. 4 CPP (CH)